Evaluating the effectiveness of Pisolithus tinctorius in enhancing the Eucalyptus’ resistance to salt stress - Mona S. Zayed; Aya G. A. Ahmed; Shawky M. Selim; Dalia A. Abd El-Fattah (AMB Express)
Abstract Afforestation projects on saline land, using Eucalyptus trees and ectomycorrhizal fungi, are crucial for restoring affected areas and promoting ecological and economic benefits, particularly in saline-affected areas. This study was conducted to isolate Pisolithus sp. and estimate its potential to improve the growth performance of Eucalyptus globulus seedlings under salt-stress conditions. Pisolithus sp. was isolated from mature sporocarps and identified through 18S rDNA. Pisolithus sp. was evaluated for its response to varying pH values, temperatures, and salinity levels. A pot experiment was conducted to assess the Pisolithus strain’s effectiveness in reducing soil salinity’s impact on the growth of Eucalyptus globulus seedlings in sandy soil. The identified Pisolithus tinctorius with an accession number of OM125275 revealed the highest mycelium dry weight of 0.09 g/100 ml medium at pH 5.8, 0.08 g/100 ml medium at 28 °C, and 0.12 g/100 ml medium at 4% NaCl. Eucalyptus globulus seedlings inoculated with Pisolithus tinctorius demonstrated significant improvement in most parameters compared to non-mycorrhizal (control) seedlings under salt stress. The seedlings inoculated with Pisolithus tinctorius and irrigated with 6 dS/m saline water revealed the highest shoot height (55.670 cm), root length (42.33 cm), shoot fresh weight (6.44 g/plant), root fresh weight (1.84 g/plant), shoot dry weight (2.37 g/plant), and root dry weight (0.810 g/plant) when compared to all treatments. Our findings suggest that selecting appropriate fungal strains is crucial for improving plant performance in saline conditions. Graphical abstract